Headmaster accountability: Study of self-concept and interpersonal communication (case study at public junior high school of Jambi province) - Yesi Elfisa; Saukani, Saukani; Firman , Firman (Indonesian Educational Administration and Leadership Journal (IDEAL), 2020)
This study aims to assess the direct effect between the variable self-concept and interpersonal communication on headmaster’s accountability of Public Junior High School. The usefulness of the research were to reveal the nature of self-concept, Interpersonal communication and the nature of headmaster accountability. This research is a quantitative study using a survey method conducted against the Headmaster of Public Junior High School In Jambi province. The sampling technique that used was the Simple Random sampling with a population of 550 and 123 samples. Three hypothesis of the study included; 1) is there any influence of self-concept toward headmaster’s accountability of Public Junior High School, 2) ) is there any influence of interpersonal communication toward headmasters’ accountability of Public Junior High School, 3) is there any influence of self-concept and interpersonal communication toward headmaster’s accountability of Public Junior High School. Analysis tools with path analysis, followed by analysis determination (R Square), partial hypothesis test (t test) and test simultan (F test), with α = 0.05. The results of that study; 1) Self-concept had positive and significant effect on the headmasters’ accountability; 2)Communication had positive and significant effect on headmasters’ accountability; and 3) Self-concept and Interpersonal Communication had positive and significant effect toward headmasters’ Accountability of Public Junior High School Jambi Province. That the better headmasters’ self-concept and Interpersonal Communication, the headmaster’s Accountability will also be getting better